Bridge Engineering - Yaghoubi, Hamid (IntechOpen, 2018)
A bridge is a structure built to span the physical obstacles without closing the way underneath, such as a body of water, valley, or road, for the purpose of providing the passage over the obstacle. Bridge engineering is an engineering discipline branching from civil engineering that involves the planning, design, construction, operation, and maintenance of bridges to ensure safe and effective transportation of vehicles, people and goods. This book Bridge Engineering includes the main topics and the basic principles of bridge engineering and provides the full scope of current information necessary for effective and cost-conscious contemporary bridge. It reflects new engineering and building developments, the most current design methods, and the latest industry standards and policies. It provides a comprehensive overview of the significant characteristics for bridge engineering. It highlights the recent advancements, requirements, improvements, and details of the latest techniques in the global market. It contains a collection of the latest research developments on the bridge engineering. It comprehensively covers the basic theory and practice in sufficient depth to provide a solid grounding to bridge engineers. It helps readers to maximize effectiveness in all facets of bridge engineering. This professional book as a credible source and a valuable reference can be very applicable and useful for all professors, researchers, engineers, practicing professionals, trainee practitioners, students and others who are interested in the bridge projects.